Respuesta :
Answer: 11(11+10)−6(6+5)=165.
Step-by-step explanation:
To evaluate the expression 11(11+10)−6(6+5), follow the order of operations (PEMDAS/BODMAS: Parentheses, Exponents, Multiplication and Division, Addition and Subtraction) to simplify:
Start by calculating the expressions within the parentheses:
11+10=21
6+5=11
Substitute the results back into the expression:
11(21)−6(11)
Perform the multiplications:
11×21=231
6×11=66
Substitute the results back into the expression:
231−66
Finally, perform the subtraction:
231−66=165
So, 11(11+10)−6(6+5)=165.
First, we can simplify the expressions inside the parentheses
We have:
[tex]11(11+10)-6(6+5) = 11\cdot21-6\cdot11[/tex]
Applying the distributive property, we get:
[tex]11(21-6)[/tex]
Simplifying, we get:
[tex]11\cdot15[/tex]
Applying the distributive property again, we have:
[tex]11\cdot10+11\cdot5[/tex]
Multiplying and adding, we have our final answer.
[tex]110+55 = \boxed{165}[/tex]
So, the answer is 165.